The environmental-sensitivity of a fluorescent ZTRS–Cd(ii) complex was applied to discriminate different types of surfactants and determine their CMC values. Issue 48 (29th May 2018) - Deng, Fei; Long, Shuangshuang; Qiao, Qinglong; Xu, Zhaochao
Abstract : One probe to distinguish four types of surfactants based on Cd(ii ) binding modes between imidic acid and amide tautomeric forms. Abstract : We have, for the first time, reported a fluorescent probe (ZTRS–C18 –Cd(ii ) complex) which discriminated four types of surfactants. This recognition was realized depending on the transformation ofZTRS–Cd 2+ binding patterns in different microenvironments formed in various types of surfactants.